Presenting a merit-oriented service compensation system model for veterans in sports - Hoseain Aeinehchi; Mohammad reza Esmaeilzadeh Ghandehari; Hoseain peymanizad; Hasan Fahim Davin (مدیریت و چشم انداز آموزش)
AbstractThe purpose of this research is to provide a model of merit service compensation system for veterans in sports. The current research is applicable-developmental and survey-type in terms of purpose. The statistical population of the present study includes all deputy ministers, directors of the general staff of the respective ministries, federations' heads and secretaries, heads and members of the directorate of federations, official members of committees such as members of the National Olympic and Paralympic Committees, the Supreme Council of Sports and heads, directors and deputies of general departments of sports and the youth of the provinces and their peers along with coaches, referees and prominent players in the field of sports are 3560 people, which was considered to be 250 people using Cochran's formula, and multi-stage stratified sampling method was used. The collection tool in this research includes a researcher-made questionnaire derived from the qualitative method. The reliability of the research was checked and confirmed using Cronbach's alpha criterion in SPSS software. Lisrel software was used to fit the conceptual model of the research. In order to confirm the final research model, confirmatory factor analysis was performed. The findings of the research showed that the research model has a good fit with the collected data. Also, in order to improve the fit indices of the model, the terms suggested in accordance with the research literature were used and finally the research model was confirmed, and the GOF value is equal to 0.62 which shows a strong fit to the model.Extended abstractIntroductionThe importance of world's current developments such as economic competition and the increasing growth of global competition (Yazdani et al, 2020), the emergence of conflict and tension between governments (Goby et al, 2015), and the consequences of critical events obliged many governments and organizations in the last decade to reform their human resource management systems, which necessitates adopting new approaches and changing the mentality of senior government managers in human resource management policies such as reward and compensation, recruitment, selection and promotion (Noti Zahi et al., 2022).Service compensation is one of the main elements of the employment relationship between individuals and organizations, and in addition to being the largest operational cost for many organizations, it is considered as a tool to increase organizational performance and sustainable competition (Ivana et al, 2019). A proper compensation management system helps business owners and managers to significantly boost employee performance by having a more active and motivated workforce (Mabaso, 2018). Service compensation has one of the most vital effects on the quality of work and the effectiveness of human capital. Compensation for services depends on the characteristics of the people who are employed. The degree of competence and expertise of the people who are hired affects the likelihood of accepting a job, the level of motivation and performance of the workforce, and the characteristics of those who stay in the organization (Bazrafshan et al, 2020). (Mohebbi et al., 2022). An organization interested in participating in a competitive market should prioritize meritocracy in its programs and try to continuously improve the competence of experts and managers. Neglecting the culture of meritocracy in the organization and not providing a suitable platform for cultivating worthy people, lack of specific criteria and legal methods in recruitment systems, appointment and promotion, and non-compliance with existing laws are among the most important factors preventing the establishment of a meritocracy system and the lack of development of a culture of meritocracy in organizations that causes discouragement and job dissatisfaction in employees (Sina & Sadati tile bani, 2022). Therefore, the researcher is trying to answer the question: what is the model of merit service compensation system for veterans in sports?Theoretical FrameworkService compensationEverything that the organization pays to employees in return for performing duties, which includes varied payment wages or allowances and in general any material and moral privileges, is called service compensation (Mohammadbagheri et al, 2022).MeritocracyMeritocracy is a management philosophy and attitude in which human resources are positioned and developed according to their efforts and inherent abilities. Meritocracy is the concept of giving a position based on merit, and not giving a position based on being the apple of somebody's eye or having a social class (Alizadeh, 2015).Erika & Gianmarco (2022) investigated promotions and productivity: the role of meritocracy and advancement. The results of the study showed that meritocratic promotions lead to higher productivity, and more so when workers expect a large increase in wages. However, when promotions are not meritocratic, increasing wage gradients reduce productivity through negative morale effects. The findings highlight the importance of considering interactions between different personnel policy instruments.Djaelani et al, (2022) investigated the impact of supervision, service compensation systems and organizational commitment on employee performance in construction service companies. The results of this research show that three independent variables partially and simultaneously have a significant effect on the performance of employees.Research methodologyThe current research is applicable-developmental and survey-type in terms of purpose. The statistical population of the present study includes all deputy ministers, directors of the general staff of the respective ministries, heads and secretaries of federations, heads and members of the directorate of federations, official members of committees such as members of the National Olympic and Paralympic Committees, the Supreme Council of Sports and heads, directors and deputies of general departments of sports and the youth of the provinces and their peers along with coaches, referees and prominent players in the field of sports are 3560 people, which was considered to be 250 people using Cochran's formula, and multi-stage stratified sampling method was used. The collection tool in this research includes a researcher-made questionnaire derived from the qualitative method.Research findingsSPSS software was used for data analysis, and Lisrel software was used to fit the research conceptual model. In order to confirm the final research model, confirmatory factor analysis was performed. The findings of the research showed that the research model has a good fit with the collected data. Also, in order to improve the fit indices of the model, the terms suggested in accordance with the research literature were used and finally the research model was confirmed and the GOF value is equal to 0.62, which shows a strong fit to the model.ConclusionThe current research was conducted with the aim of presenting a merit-based service compensation system model for veterans in sports. This research is consistent with the results of Erika & Gianmarco (2022), Djaelani et al, (2022), Alison et al, (2021), Sina & Sadati tile bani (2022), Mohebi et al, (2022), Moradzadeh et al, (2022), Moghimi Firoozabad & Hamdollahi (2022), Fani et al, (2021), Maleki et al, (2019), and Zarei et al, (2020).Erika & Gianmarco (2022) showed that meritocratic promotions lead to higher productivity, and more so when workers expect a large increase in wages. However, when promotions are not meritocratic, increasing wage gradients reduce productivity through negative morale effects. The findings highlight the importance of considering interactions between different personnel policy instruments.Based on the results of the research, it is suggested that sports programs with a detailed planning and using veterans in sports help the education and development of these sports in their province. Another activity that sports programs can do is to help the interaction of cities that have social divergence. Therefore, if the sports programs of the province help to organize friendly games between these cities or express the common cultural and sports points of these cities, then they will help the interaction of these cities a lot.